¡Voy en camino! - Rojas-Primus, Constanza; Robles, Ana (Open textbook library., 2023)
¡Voy en camino! means “I’m on my way” in Spanish. Since learning an additional language and the culture is a journey in itself, ¡Voy en camino! captures the voyage to get there. ¡Voy en camino! has been created to serve the first two introductory Spanish language courses at Kwantlen Polytechnic University (KPU) and to solidify our commitment to Zero Textbook Cost (ZTC). All units of study are designed to be interactive with embedded audio, videos and links for learners to practice the material along the way. Learners can self-pace and self-test their knowledge both individually and with the assistance of an instructor. ¡Voy en camino! has plenty of opportunities to practice writing and speaking with downloadable capabilities becoming a Spanish teaching and learning tool that promotes and supports sustainable renewable learning. With its digital format and open publication ¡Voy en camino! is also meant to join the Spanish teaching open education community and provide access to learning to interested users along the way.